2001
DOI: 10.1093/jn/131.6.1803
|View full text |Cite
|
Sign up to set email alerts
|

Hamsters Predisposed to Sucrose-Induced Cholesterol Gallstones (LPN Strain) Are More Resistant to Excess Dietary Cholesterol than Hamsters That Are Not Sensitive to Cholelithiasis Induction

Abstract: We compared the effects of cholesterol feeding in male hamsters from two strains with different propensities to sucrose-induced cholelithiasis; Laboratoire de Physiologie de la Nutrition (LPN) hamsters are predisposed to developing biliary cholesterol gallstones, whereas Janvier (JAN) hamsters are not. When fed a basal control diet, LPN hamsters had a lower cholesterolemia (-21%, P = 0.01) than JAN hamsters, and a higher activity of 3-hydroxy-3-methyl glutaryl coenzyme A reductase in liver (+148%, P = 0.018) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 56 publications
1
10
0
2
Order By: Relevance
“…This study also demonstrated similar reciprocal changes in parenchymal and Kupffer cell expression after cholesterol feeding (212). However, studies with hamsters and mice did not find that hepatic SR-BI levels and/or HDL cholesteryl ester transport were regulated by changes in dietary cholesterol (237)(238)(239). In addition, a deficiency of plasma HDL in apoA-I KO mice does not increase hepatic SR-BI expression (240).…”
Section: A Livermentioning
confidence: 63%
“…This study also demonstrated similar reciprocal changes in parenchymal and Kupffer cell expression after cholesterol feeding (212). However, studies with hamsters and mice did not find that hepatic SR-BI levels and/or HDL cholesteryl ester transport were regulated by changes in dietary cholesterol (237)(238)(239). In addition, a deficiency of plasma HDL in apoA-I KO mice does not increase hepatic SR-BI expression (240).…”
Section: A Livermentioning
confidence: 63%
“…Final lipid content of the diet was 14 to 15% and that of CT was Ͻ0.1%. The cholesterol content of the "linseed" diet (0.064%) was not adjusted to that of the "butter" diet (0.097%) because the LPN strain is known to exhibit a low metabolic responsiveness to dietary cholesterol [34]. Moreover, previous studies in the hamster showed that, in this range of cholesterol content, the effects of dietary cholesterol alone are minor in regard to that of the saturated vs. polyunsaturated FA [35,36].…”
Section: Animals and Dietsmentioning
confidence: 99%
“…34 However, studies with hamsters and mice did not find that hepatic SR-BI levels or HDL cholesteryl ester transport were regulated by changes in dietary cholesterol. [47][48][49] In the liver, a soluble multiple PDZ-domain-containing protein, PDZK1 (also called CLAMP), binds to the cytoplasmic C-terminus of SR-BI 38 and seems to play an important role in controlling the intracellular transport, polarized expression, stability, and activity of SR-BI. 38,50 Coexpression of PDZK1/CLAMP with SR-BI in transfected cells affects both the stability of SR-BI as well as the efficiency of conversion of HDL cholesteryl esters taken up via SR-BI to intracellular unesterified cholesterol.…”
mentioning
confidence: 99%